Combined effects of ozone and drought stress on the emission of biogenic volatile organic compounds from Quercus robur L - Peron, Arianna; Kaser, Lisa; Fitzky, Anne Charlott; Graus, Martin; Halbwirth, Heidi; Greiner, Jürgen; Wohlfahrt, Georg; Rewald, Boris; Sandén, Hans; Karl, Thomas (Biogeosciences, 2021)
Drought events are expected to become more frequent with climate change. To predict the effect of plant emissions on air quality and potential feedback effects on climate, the study of biogenic volatile organic compound emissions under stress is of great importance. Trees can often be subject to a combination of abiotic stresses, for example due to drought or ozone. Even though there is a large body of knowledge on individual stress factors, the effects of combined stressors are not much explored. This study aimed to investigate changes of biogenic volatile organic compound emissions and physiological parameters in Quercus robur L. during moderate to severe drought in combination with ozone stress. Results show that isoprene emissions decreased while monoterpene and sesquiterpene emissions increased during the progression of drought. We exposed plants with daily ozone concentrations of 100 ppb for 1 h for 7 d, which resulted in faster stomatal closure (e.g., a mean value of −31.3 % at an average stem water potential of −1 MPa), partially mitigating drought stress effects. Evidence of this was found in enhanced green leaf volatiles in trees without ozone fumigation, indicating cellular damage. In addition we observed an enhancement in (C8H8O3)H+ emissions likely corresponding to methyl-salicylate in trees with ozone treatment. Individual plant stress factors are not necessarily additive, and atmospheric models should implement stress feedback loops to study regional-scale effects.